Overview of impact assessment methodologies - Anandajayasekeram, P.; Babu, Suresh Chandra (CAB International, 2007)
The ultimate interest of investors in agricultural research and Development (R&D) is the extent to which their investment eventually bears a positive outcome on the lives of the poor and hungry people of developing nations without seriously harming the natural resource base. Consequently, most donors, governments and financiers of agricultural and natural resource research focus on outcome and impact assessment as a major step in their strategy. In impact assessment of R&D investments, one needs to differentiate between the research results and the contribution of research to Development (i.e. the people-level impact). Moreover, both of these aspects should be addressed simultaneously. This chapter summarizes the various methods and techniques used in R&D using a comprehensive framework that addresses intermediate product, direct product and people-level impact simultaneously. Owing to the wide-ranging implications of agricultural research results to society, no single technique or method is sufficient to adequately address the impact. However, there is consensus that the most appropriate approaches to impact assessment should involve a mixture of both qualitative and quantitative methods and active participation of the beneficiaries. Case studies are also essential for further refining the approaches and lessons learned. The chapter concludes by outlining suggested best practices in understanding impact assessment of agricultural R&D investments.